Physiological efficacy of the amino acid-based biostimulants Pepton 85/16, Pepton origin, and Nutriterra in lettuce grown under optimal and reduced synthetic nitrogen fertilization - Atero-Calvo, Santiago; Navarro-León, Eloy; Polo, Javier; Ruiz, Juan Manuel (Frontiers in Plant Science, 2025)
Improving nitrogen (N) use efficiency (NUE) is a key objective in sustainable agriculture, particularly for leafy vegetables such as lettuce, which require high N inputs. Biostimulants offer a promising strategy for enhancing crop performance while reducing fertilizer dependency. In this study, we evaluated the effects of three amino acid-based biostimulants, Pepton 85/16, Pepton Origin, and Nutriterra, on lettuce growth and NUE under three N fertilization levels (100%, 70%, and 40% of the recommended dose). All biostimulants improved shoot biomass, leaf area, and physiological performance, including photosynthetic rate (A) and key N assimilation parameters. Nutriterra was the most effective under full N supply, enhancing both productivity and water use efficiency (WUE) while reducing leaf nitrate concentration, contributing to improved crop quality. Under N-limited conditions, Pepton 85/16 consistently outperformed the other products, especially at 70% N, where it restored and even exceeded the biomass levels observed under optimal N. This effect was associated with enhanced nitrate reductase (NR) and glutamine synthetase (GS) activity, increased protein and amino acid concentrations, and higher organic N levels. While Pepton Origin also showed beneficial effects under N limitation, its impact was less pronounced. Overall, the targeted use of these biostimulants represents an effective strategy for maintaining productivity and reducing synthetic N fertilization in lettuce cultivation systems.